Preparation method and application of long-acting photocatalytic antifouling coating material
Patent Information
- Application Number
- CN202610641446.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-11
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2046-05-11
AI Technical Summary
[0005]为了解决上述技术问题,本发明提供一种长效型光催化防污涂层材料的制备方法和应用,以解决现有Cu2O基光催化防污材料载流子复合速率快、光腐蚀稳定性差、铜离子暴释失效,以及有机硅复合涂层填料分散性差、界面结合薄弱、抗菌防污周期短、无法兼顾高效杀菌与长效抗粘附的问题
本发明通过构建Ag@CuGaO异质结结构,有效整合Ga掺杂引起的小尺寸效应与Ag表面等离子体共振特性,显著增强可见光吸收能力与载流子分离效率,使活性氧(ROS)生成速率大幅提升,对典型海洋细菌(如铜绿假单胞菌、金黄色葡萄球菌)的抑菌率达99.9%,突破传统光催化材料在弱光环境下的效能瓶颈。
Smart Images

Figure CN122278341B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of marine antifouling coating technology, and more specifically, relates to a method for preparing and applying a long-lasting photocatalytic antifouling coating material. Background Technology
[0002] Marine resources are a crucial foundation for future economic development, making their development and utilization paramount. However, marine equipment faces the severe challenge of marine fouling, making antifouling measures for materials in marine environments essential. Coating protection is a commonly used industrial method for metal antifouling. By applying organic coatings to metal surfaces, the penetration of corrosive media such as moisture, oxygen, and chloride ions can be prevented, thus providing excellent protection for the metal materials. Filler modification is an important method for modifying organic coatings; currently, the addition of nanofillers is frequently used to improve coating performance.
[0003] Cuprous oxide (Cu2O), as a promising photocatalytic antifouling material, offers a new path for developing environmentally friendly marine antifouling technologies due to its visible light-driven characteristics and inherent ion-release bactericidal mechanism. However, this material faces multiple bottlenecks in practical applications. At the intrinsic performance level, the rapid carrier recombination phenomenon in the Cu2O crystal structure significantly weakens photocatalytic efficiency, resulting in insufficient reactive oxygen species generation to meet the requirements for efficient sterilization. More seriously, under the coupled effect of aquatic environment and light, irreversible photocorrosion occurs on the Cu2O surface, oxidizing cuprous ions in the crystal lattice to a divalent state, causing structural collapse and functional failure. When attempting to integrate Cu2O as a functional filler into antifouling coating systems, its application compatibility issues become even more prominent—the gradual disintegration of the material in aqueous media induces excessive release of copper ions. While this initially kills microorganisms quickly, the burst release effect not only shortens the antibacterial cycle but also damages the integrity of the coating's polymer network, leading to coating powdering or cracking. In addition, micron-sized Cu2O particles have poor dispersion stability in organic resins and are prone to agglomeration and sedimentation, causing local functional failure of the coating.
[0004] Meanwhile, the organosilicon antifouling coating, serving as the Cu2O carrier matrix, suffers from significant engineering defects: the introduction of nanofillers, without adequate interface design, can exacerbate stress concentration; its static antifouling ability is insufficient against microbial metabolites, and long-term immersion easily leads to the formation of biofilm "bridging points" on the surface, ultimately resulting in large-scale biofouling. While current composite coating technologies aim to improve overall performance, balancing filler functionality, dispersion stability, and resin matrix durability remains a core challenge hindering the practical application of photocatalytic antifouling coatings. Faced with the triple dilemma of Cu2O material stability defects, coating carrier interface failure risks, and the difficulty in simultaneously meeting long-term antifouling requirements, there is an urgent need to explore innovative solutions that combine atomic-level structure control with macroscopic interface enhancement. Summary of the Invention
[0005] To address the aforementioned technical problems, this invention provides a method for preparing and applying a long-lasting photocatalytic antifouling coating material. This addresses the issues of existing Cu2O-based photocatalytic antifouling materials, such as rapid carrier recombination rate, poor photocorrosion stability, and copper ion burst failure, as well as the poor dispersibility of fillers in organosilicon composite coatings, weak interfacial bonding, short antibacterial and antifouling cycles, and the inability to simultaneously achieve both high-efficiency sterilization and long-lasting anti-adhesion.
[0006] This invention provides a long-lasting photocatalytic antifouling coating material, the material comprising an Ag@CuGaO heterojunction photocatalytic antifouling agent and an organosilicon antifouling coating; The Ag@CuGaO heterojunction material is a nanocubic structure formed by modifying CuGaO with Ag nanoparticles, prepared by a modified wet chemical reduction method, with a silver loading of 0.5~10 wt%. The organosilicon antifouling coating, by weight, consists of 100 parts of organosilicon resin matrix and 1-5 parts of Ag@CuGaO heterojunction material; Ag nanoparticles form a tight heterogeneous interface on the CuGaO surface, which synergistically broadens the light absorption range and improves the carrier separation efficiency. The material has broad-spectrum and long-lasting antibacterial properties against Staphylococcus aureus and Pseudomonas aeruginosa.
[0007] Furthermore, the present invention provides a method for preparing the Ag@CuGaO heterojunction photocatalytic antifouling agent, comprising the following steps: Sodium citrate was dissolved in deionized water and magnetically stirred to form a solution. Copper sulfate pentahydrate and gallium nitrate were added sequentially and stirred continuously to dissolve. Sodium hydroxide solution was added and stirring continued to form a colloidal suspension. Ascorbic acid solution was added dropwise until the suspension turned yellow. Silver nitrate was added and stirred to react. The precipitate was collected by centrifugation. The precipitate was washed with deionized water and acetone and dried under vacuum to obtain Ag@CuGaO heterojunction photocatalytic antifouling agent.
[0008] Preferably, the following mixture is used: 7 mmol sodium citrate, 450 mL deionized water, 3 mmol copper sulfate pentahydrate, 0.3 mmol gallium nitrate, 3.6 mL sodium hydroxide solution, 3.6 mL ascorbic acid solution (concentration 0.5~1.5 mol / L), and 0.1~1 mmol silver nitrate. Sodium citrate is dissolved and stirred for 5~10 min, and the metal salt is dissolved and stirred for 10~15 min. NaOH is added and stirred for 10~15 min. After adding silver nitrate, the reaction proceeds for 30~60 min, centrifuged at 3000~8000 r / min, and vacuum dried at 60~80℃ for 6~12 h. The precipitate is washed three times with deionized water and once with acetone.
[0009] Furthermore, the present invention provides a method for preparing the long-lasting photocatalytic organosilicon antifouling coating, using low-carbon steel as a substrate, comprising the following steps: after surface pretreatment of the substrate, Ag@CuGaO heterojunction antifouling agent is dispersed in acetone solvent and ultrasonically treated, and organosilicon resin is added and ultrasonic treatment is continued; after adding curing agent and stirring evenly, degassing treatment is performed, and the coating is applied to the substrate surface by spin coating process, and cured and crosslinked at room temperature to obtain the organosilicon antifouling coating.
[0010] Preferably, the low-carbon steel substrate has a size of 2×2cm and is pretreated by gradient sanding, ultrasonic cleaning, and deionized water rinsing; the Ag@CuGaO addition amount is 0.5wt%~5wt%, acetone dispersion and ultrasonication for 30min, followed by ultrasonication for 60min after adding resin; the curing agent addition amount is 1%~3% of the silicone resin mass, stirring for 5~10min, and degassing for 20min; the spin coating speed is 100rpm, the duration is 30s, and the curing time is 12~24h at room temperature.
[0011] Furthermore, the present invention provides the application of the long-lasting photocatalytic antifouling coating material, applying the Ag@CuGaO heterojunction material and the organosilicon antifouling coating to the field of biofouling prevention on the metal surface of marine facilities; the coating is a composite structure in which nanocomposite materials are uniformly dispersed in organosilicon resin and tightly bonded to a low-carbon steel substrate.
[0012] Compared with the prior art, the present invention has the following beneficial effects: This invention effectively integrates the small size effect caused by Ga doping with the plasmon resonance characteristics of Ag surface by constructing an Ag@CuGaO heterojunction structure, significantly enhancing visible light absorption and carrier separation efficiency, thereby greatly increasing the generation rate of reactive oxygen species (ROS). It achieves a 99.9% inhibition rate against typical marine bacteria (such as Pseudomonas aeruginosa and Staphylococcus aureus), breaking through the performance bottleneck of traditional photocatalytic materials in low-light environments.
[0013] This invention relates to an organosilicon antifouling coating prepared based on this heterojunction material. Through the uniform dispersion and optimized addition of Ag@CuGaO nanocubes in a resin matrix, it simultaneously achieves the dual functions of surface anti-adhesion and contact sterilization, realizing an integrated antifouling and sterilization synergistic antifouling mechanism. It forms a long-lasting protective layer on the surface of low-carbon steel-based marine facilities such as ship decks and offshore pipelines, effectively inhibiting biofilm formation and microbial adhesion.
[0014] The preparation process described in this invention is both green and economical: the improved wet chemical reduction method precisely controls the silver loading at 0.5-2.0 wt%, significantly reducing the amount of precious metals used; the organosilicon resin matrix is compatible with conventional processes such as spin coating and spraying, and can form a uniform coating on complex curved substrates, making it suitable for the long-term protection needs of large-scale marine engineering facilities. Attached Figure Description
[0015] Figure 1 This is the ultraviolet-visible absorption spectrum provided in the embodiments of the present invention; Figure 2 This is a graph showing the photoelectrocatalytic activity test results provided in an embodiment of the present invention; Figure 3 This is a graph showing the sterilization performance test results provided in an embodiment of the present invention; Figure 4 This is a graph showing the test results of the coating water absorption rate provided in an embodiment of the present invention; Figure 5 These are SEM images of the surface morphology of the coating before and after sterilization, provided in an embodiment of the present invention. Figure 6 This is a transmission electron microscope (TEM) image of the Ag@CuGaO heterojunction photocatalytic antifouling agent of the present invention. Detailed Implementation
[0016] The present invention will be further described in detail below with reference to specific embodiments. These embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Any equivalent substitutions or simple modifications made based on the technical solutions of the present invention shall fall within the scope of protection of the present invention.
[0017] This invention discloses a method for preparing and applying a long-lasting photocatalytic antifouling coating material. The core of the method is the wet chemical reduction of Ag@CuGaO heterojunction photocatalytic antifouling agent, and the preparation of an antifouling coating by combining the antifouling agent with organosilicon resin. The Ag@CuGaO heterojunction material integrates the small size effect of Ga doping with the surface plasmon properties of Ag, with a silver loading of 0.5~10wt%; the Ag@CuGaO addition amount in the organosilicon antifouling coating is 1~5 parts by weight, which is suitable for preventing biofouling on the metal surfaces of marine facilities.
[0018] All raw materials used in this invention are commercially available industrial-grade products without special treatment; the equipment used are standard laboratory equipment such as magnetic stirrers, centrifuges, vacuum drying ovens, ultrasonic instruments, and spin coaters.
[0019] Example 1, Preparation of Ag@CuGaO heterojunction photocatalytic antifouling agent: Accurately weigh the following raw materials: sodium citrate 7 mmol, deionized water 450 mL, copper sulfate pentahydrate 3 mmol, gallium nitrate 0.3 mmol, sodium hydroxide solution 3.6 mL, 1.5 mol / L ascorbic acid solution 3.6 mL, silver nitrate 0.3 mmol; Add sodium citrate to deionized water and stir magnetically for 10 minutes until completely dissolved to form a homogeneous solution; Add copper sulfate pentahydrate and gallium nitrate to the above solution in sequence, and stir magnetically for 10 minutes until the metal salt is completely dissolved; Rapidly inject sodium hydroxide solution and continuously stir magnetically for 15 minutes to form a stable colloidal suspension. Add ascorbic acid solution drop by drop, stirring until the suspension turns completely yellow, then stop adding. Add silver nitrate and stir magnetically for 60 minutes to complete the synthesis of the heterostructure; Place the reaction solution in a centrifuge and centrifuge at 8000 r / min, then collect the precipitate at the bottom. The precipitate was washed three times with deionized water and once with acetone to remove residual reactants and impurities. After washing, the precipitate was placed in a vacuum drying oven at 60℃ and dried for 6 hours. After grinding, Ag@CuGaO heterojunction photocatalytic antifouling agent was obtained with a silver loading of 2.0 wt%.
[0020] Example 2, Preparation of Cu2O-containing organosilicon antifouling coating (control coating): Substrate pretreatment: Select a 2×2cm low carbon steel substrate, and successively polish it with 100 grit, 200 grit and 500 grit sandpaper, ultrasonically clean it for 15 minutes, rinse it with deionized water, and let it dry for later use. Dispersion treatment: Weigh 2 wt% Cu2O nanomaterials, disperse them in acetone solvent, and sonicate for 30 min to form a uniform dispersion; Resin compounding: The organosilicon resin matrix is gradually added to the dispersion, and ultrasonic treatment is continued for 60 minutes to ensure that the filler and resin are fully mixed; Curing and degassing: Add curing agent at 3% of the mass of silicone resin and stir magnetically for 10 min; then degas for 20 min to eliminate air bubbles in the system; Spin coating film formation: The mixture is coated onto the clean low-carbon steel substrate surface using a spin coater at a speed of 100 rpm for 30 seconds. Room temperature curing: After coating, the substrate is placed at room temperature and crosslinked for 24 hours to obtain Cu2O modified organosilicon antifouling coating.
[0021] Example 3, Preparation of CuGaO-containing organosilicon antifouling coating (control coating): The only difference between this embodiment and Embodiment 2 is that Cu2O is replaced with an equal mass of CuGaO nanomaterials, while the other raw materials, process parameters, and preparation steps are completely identical, resulting in a CuGaO-modified organosilicon antifouling coating.
[0022] Example 4, Preparation of an organosilicon antifouling coating containing Ag@CuGaO (Preferred embodiment of the present invention): The only difference between this embodiment and Example 2 is that Cu2O is replaced with an equal mass of Ag@CuGaO heterojunction antifouling agent prepared in Example 1. All other raw materials, process parameters, and preparation steps are completely the same, and Ag@CuGaO modified long-lasting photocatalytic organosilicon antifouling coating is obtained.
[0023] Comparative Example 1: Preparation of pure Cu₂O nanomaterials: The difference between this comparative example and Example 1 is that gallium nitrate and silver nitrate are not added, the amount of ascorbic acid solution is adjusted to 3.0 mL, and the rest of the preparation steps and process parameters are completely the same, so that pure Cu2O nanomaterials are obtained.
[0024] Comparative Example 2, Preparation of Ag-modified Cu2O nanomaterials: The difference between this comparative example and Example 1 is that gallium nitrate is not added, the amount of ascorbic acid solution is adjusted to 3.0 mL, and the rest of the preparation steps and process parameters are completely the same, thus obtaining Ag@Cu2O nanomaterials.
[0025] Comparative Example 3: Preparation of a pure organosilicon blank coating: The difference between this comparative example and Example 2 is that no nano-functional fillers are added, and the silicone resin and curing agent are directly compounded. The remaining preparation steps and process parameters are completely the same, and a pure silicone blank coating is obtained.
[0026] Performance Tests and Results: Standardized performance tests were conducted on the above-described embodiments and comparative samples. The test items included UV-Vis absorption performance, photoelectrocatalytic activity, sterilization performance, coating water absorption rate, and surface antibacterial morphology. The test results are as follows: The UV-Vis absorption performance test showed that the Ag@CuGaO material in Example 1 had a significantly improved absorption intensity in the visible light range of 450~800nm; the absorption edge of pure Cu2O in Comparative Example 1 was 560nm, and the absorption edge of Ag@Cu2O in Comparative Example 2 was red-shifted to 600nm; this proves that Ga doping and Ag heterostructure synergistically broaden the light absorption range of the material and improve its visible light response.
[0027] The photoelectrocatalytic activity test of Example 1 showed that the sample had the largest electrochemical active surface area and its photoelectrocatalytic activity was significantly better than that of Comparative Example 1 and Comparative Example 2; this proves that the heterojunction structure effectively inhibits carrier recombination and improves the efficiency of photocatalytic reaction.
[0028] The sterilization performance of nanomaterials was tested using Staphylococcus aureus and Pseudomonas aeruginosa as test strains. Comparative Example 1 showed a decrease in the number of colonies, Comparative Example 2 showed improved antibacterial performance, and the sample in Example 1 showed no colony growth, with an inhibition rate of 99.9%, demonstrating broad-spectrum and highly efficient bactericidal performance.
[0029] The lower the water absorption rate of the coating, the better the hydrophobic and antifouling performance of the coating. The water absorption rate of the coating in Example 4 was significantly lower than that in Examples 2, 3 and Comparative Example 3, which proves that Ag@CuGaO modification optimizes the hydrophobic properties of the coating surface and reduces the probability of microbial adhesion.
[0030] SEM characterization of the antibacterial morphology of the coating surface showed that: in Comparative Example 3, bacteria were intact and multiplied in large quantities on the blank coating surface; in Example 4, the bacterial structure on the coating surface was damaged, collapsed and ruptured, achieving efficient contact sterilization without biofilm formation.
[0031] Application effect verification: The organosilicon antifouling coating prepared in Example 4 was subjected to long-term testing in a simulated marine environment: when the amount of Ag@CuGaO added was 2-3 parts by weight, the bacterial adhesion rate of the coating was the lowest, and the immediate sterilization rate reached 99%; after continuous immersion for 60 days, the antibacterial rate of the coating was still >90%, and there was no obvious powdering, cracking, or peeling. It has integrated antifouling performance with high efficiency sterilization, anti-adhesion, and long-term stability, and can be widely used for biofouling prevention on the metal surfaces of marine facilities such as ships and marine pipelines.
[0032] The embodiments of the present invention are given for illustrative and descriptive purposes only, and are not intended to be exhaustive or to limit the invention to the forms disclosed. Many modifications and variations will be apparent to those skilled in the art. The embodiments were chosen and described in order to better illustrate the principles and practical application of the invention, and to enable those skilled in the art to understand the invention and to design various embodiments with various modifications suitable for a particular purpose.
Claims
1. A long-lasting photocatalytic antifouling coating, characterized in that, Including Ag@CuGaO heterojunction photocatalytic antifouling agent and organosilicon; The Ag@CuGaO heterojunction photocatalytic antifouling agent is a nanocubic structure formed by modifying CuGaO with Ag nanoparticles, with a silver loading of 0.5~10wt%, and is prepared by wet chemical reduction method; The organosilicon antifouling coating comprises, by weight, 100 parts of organosilicon resin matrix and 1-5 parts of Ag@CuGaO heterojunction photocatalytic antifouling agent; The Ag nanoparticles form a tight heterogeneous interface with CuGaO, which synergistically broadens the light absorption range and improves the carrier separation efficiency. The coating has broad-spectrum antibacterial properties against Staphylococcus aureus and Pseudomonas aeruginosa.
2. A method for preparing an Ag@CuGaO heterojunction photocatalytic antifouling agent, used to prepare the antifouling agent according to claim 1, characterized in that, Includes the following steps: S1. Dissolve 7 mmol of sodium citrate in 450 mL of deionized water and stir magnetically for 5-10 min to form a solution; S2. Add 3 mmol copper sulfate pentahydrate and 0.3 mmol gallium nitrate in sequence, and stir magnetically for 10-15 minutes until completely dissolved; S3. Inject 3.6 mL of sodium hydroxide solution and stir magnetically for 10-15 min to form a colloidal suspension; S4. Add 3.6 mL of ascorbic acid solution with a concentration of 0.5~1.5 mol / L dropwise until the suspension turns yellow; S5. Add 0.1~1 mmol of silver nitrate and stir magnetically for 30~60 min to carry out the reaction; S6. Collect the precipitate by centrifugation at 3000~8000r / min. Wash the precipitate three times with deionized water and once with acetone. S7. Vacuum drying at 60~80℃ for 6~12h yields Ag@CuGaO heterojunction photocatalytic antifouling agent.
3. A method for preparing a long-lasting photocatalytic organosilicon antifouling coating, used to prepare the coating of claim 1, characterized in that, Using low-carbon steel as a base, the process includes the following steps: T1. Substrate pretreatment: 2×2cm low carbon steel is sanded with sandpaper gradient, ultrasonically cleaned, and rinsed with deionized water before use. T2. Dispersion and mixing: Disperse 0.5wt% to 5wt% of Ag@CuGaO heterojunction photocatalytic antifouling agent in acetone, sonicate for 30 min, add organosilicon resin and continue sonication for 60 min. T3. Curing and degassing: Add curing agent accounting for 1% to 3% of the weight of silicone resin, stir for 5 to 10 minutes, and degas for 20 minutes to eliminate bubbles; T4. Coating and curing: The coating is applied to the substrate surface using a spin coating process and cured at room temperature for 12-24 hours to obtain an organosilicon antifouling coating.
4. The preparation method according to claim 3, characterized in that, The spin coating process parameters in step T4 are: spin speed 100 rpm, coating duration 30 s.
5. The long-lasting photocatalytic antifouling coating according to claim 1, characterized in that, When the Ag@CuGaO heterojunction photocatalytic antifouling agent is added in an amount of 2-3 parts by weight, the coating has the lowest bacterial adhesion rate, an immediate sterilization rate of 99%, and an antibacterial rate of >90% after 60 days in a simulated marine environment.
6. The preparation method according to claim 2, characterized in that, In step S5, the amount of silver nitrate used is 0.3 mmol, and the concentration of ascorbic acid solution is 1.5 mol / L.
7. The preparation method according to claim 2, characterized in that, In step S6, the centrifugation speed is 8000 r / min, and in step S7, the vacuum drying conditions are 60℃ and drying for 6 hours.
8. The preparation method according to claim 3, characterized in that, In step T3, the amount of curing agent added is 3% of the mass of the silicone resin, and the stirring time is 10 minutes.
9. The application of the long-lasting photocatalytic antifouling coating according to claim 1, characterized in that, The antifouling coating is applied to the field of biofouling prevention on the metal surfaces of marine facilities.
10. The application according to claim 9, characterized in that, The antifouling coating is a composite structure in which Ag@CuGaO heterojunction photocatalytic antifouling agent is uniformly dispersed in organosilicon resin. It is tightly bonded to the low-carbon steel substrate and has photocatalytic sterilization, antibacterial adhesion and long-lasting antifouling properties.
Citation Information
Patent Citations
Antibacterial low-surface-energy composite marine antifouling coating material, preparation method and coating
CN117986995A
Marine environment-friendly efficient antifouling agent and preparation method of composite coating of marine environment-friendly efficient antifouling agent
CN121851769A